2014
DOI: 10.1074/jbc.m113.497438
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Structure and Double Electron-Electron Resonance of the Zebrafish Voltage-dependent Anion Channel 2 Reveal an Oligomeric Population

Abstract: Background: Biochemical characterization of voltage-dependent anion channel 2 (VDAC2) is limited due to an inability to obtain functional protein. Results:The crystal structure of VDAC2 suggests a dimer interface that is confirmed by double electron-electron resonance and cross-linking. Conclusion: zfVDAC2 has a fractional dimeric population. Significance: VDAC isoforms are structurally similar, but this study has identified a number of hot spots that require further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
175
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(194 citation statements)
references
References 45 publications
18
175
1
Order By: Relevance
“…Fortunately, the zfV2 structure has recently become available (37), and our data showed that zfV2, like mV2, supports the Bak/tBid pathway (Fig. 2).…”
Section: Structural Implications Of the Domains Identified By Mutagensupporting
confidence: 54%
See 4 more Smart Citations
“…Fortunately, the zfV2 structure has recently become available (37), and our data showed that zfV2, like mV2, supports the Bak/tBid pathway (Fig. 2).…”
Section: Structural Implications Of the Domains Identified By Mutagensupporting
confidence: 54%
“…The only crystallography study of V2 used zebrafish V2 (zfV2) that had >90% sequence similarity to mammalian V2. This work revealed few differences between V1 and V2, mostly confined to the cytoplasmic loops (37).…”
Section: Significancementioning
confidence: 79%
See 3 more Smart Citations